2021
DOI: 10.3389/fmed.2021.671945
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function Is Not Related to Brain Amyloid Burden on PET Imaging in The 90+ Study Cohort

Abstract: Cognitive decline is common in chronic kidney disease (CKD). While the evidence of vascular cognitive impairment in this population is robust, the role of Alzheimer's pathology is unknown. We evaluated serum cystatin C-estimated glomerular filtration rate (eGFR), brain amyloid-β positron emission tomography (PET) imaging, and cognitive function in 166 participants from The 90+ Study. Mean age was 93 years (range 90-107) and 101 (61%) were women; 107 participants had normal cognitive status while 59 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…43 Furthermore, neuroimaging studies have suggested that people with impaired KF have more microinfarcts, 44 lacunar infarcts, 45 white matter lesions, [45][46][47][48] infratentorial microbleeds, 49 brain atrophy, 50,51 and cortical structure alterations, 48,52 but not brain Aβ burden. 53 Our study concluded that impaired KF is associated with a higher burden of CAA pathologies in the brain, but not AD pathologies, suggesting that vascular lesions may underlie the association between KF and dementia.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…43 Furthermore, neuroimaging studies have suggested that people with impaired KF have more microinfarcts, 44 lacunar infarcts, 45 white matter lesions, [45][46][47][48] infratentorial microbleeds, 49 brain atrophy, 50,51 and cortical structure alterations, 48,52 but not brain Aβ burden. 53 Our study concluded that impaired KF is associated with a higher burden of CAA pathologies in the brain, but not AD pathologies, suggesting that vascular lesions may underlie the association between KF and dementia.…”
Section: Discussionmentioning
confidence: 54%
“…Another study, which explored the impact of CKD on cerebral amyloid‐β (Aβ) depositions, reported that perivascular Aβ deposits were detected in the direct vicinity of small vessel wall damage among up to 69% of all human cases 43 . Furthermore, neuroimaging studies have suggested that people with impaired KF have more microinfarcts, 44 lacunar infarcts, 45 white matter lesions, 45–48 infratentorial microbleeds, 49 brain atrophy, 50,51 and cortical structure alterations, 48,52 but not brain Aβ burden 53 . Our study concluded that impaired KF is associated with a higher burden of CAA pathologies in the brain, but not AD pathologies, suggesting that vascular lesions may underlie the association between KF and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Further study also gave 308 individuals aged 90 or older a PET scan and obtained the brain indices of Aβ deposition using a statistically defined region of interest (statROI), and found that PET statROI was not correlated with cystatin C and eGFR, indicating an independent association between cognition and chronic kidney disease (CKD), and the CKD-associated cognitive dysfunction largely reflects vascular rather than Aβ pathology (Lau et al, 2021). Second, the correlation between serum cystatin C and cognitive function may not only depend on kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…A post-mortem study of 50 patients on chronic haemodialysis found no increase in Alzheimer's disease pathology 4 , and a neuropathology study of the brains of 40 deceased people with CKD noted a high prevalence of arteriolosclerosis (73%) and no evidence of an association with Alzheimer's neuropathology 5 . In a cohort of 166 community-dwelling participants from The 90+ Study with a mean age of 93 years, we reported no association between cystatin C-based eGFR and brain amyloid-β burden assessed using positron emission tomography imaging 7 .…”
mentioning
confidence: 76%